El viejo soldado by Héctor Tizón. Otherness as a way of finding identity. - Domínguez Gutiérrez, M. Carmen (Oltreoceano - Rivista sulle migrazioni, 2024)
The Argentine writer Héctor Tizón (1929-2012) wrote the novel El viejo soldado in 1981, during his exile in Madrid. It is a text with strong autobiographical overtones, which remained unpublished until 2002 at the author’s own wish. The novel, as Ana Príncipi maintains, raises the problem of the preservation of a subjectivity in a situation of exile. Raúl is a young Argentine who, after the military coup in his country, goes into exile in Spain. To survive and support his family, he works as a writer in the pay of an old Francoist determined to publish his memoirs. To the experience of exile, already traumatic, Raúl will have to add the humiliation of lending his pen to someone who represents the same values that have led him to that situation. But it is, above all, his coexistence with his antagonist that causes deep fissures in the story that he has constructed of his own life. According to Paul Ricoeur (2006), man, to understand himself, must narrate his own story. Only this account of oneself grants identity to the subject. Now, this «narrative identity» (Ricoeur 997) is a dynamic process in which, from the present, the subject chooses the events, experiences and interactions with others that nourish and give meaning to the plot of his story and that help him to understand himself and be understood. It is an eternal process of resignification of one’s own self over time. From his present in exile and the confrontation with the old soldier, for Raúl his present and past life acquires another reading. This resignification of his own identity will lead him to an extreme decision: that of murdering the old man because his existence reminds him of his failure, but, above all, to end at the part of “the other” that he discovered in himself.